Comparative Study of the Electrical Characteristics of Different Photovoltaic Modules in Outdoor Environment - Jatoi, A. R.; Samo, S. R.; Jakhrani, A. Q. (Engineering, Technology & Applied Science Research, 2019)
The electrical characteristics of photovoltaic (PV) modules are affected by solar radiation and module temperature in outdoor environment. It was found that polycrystalline gained a yearly 0.50°C more average module temperature than monocrystalline. Non-crystalline amorphous modules got a yearly 0.83°C more average temperature than thin film modules. The attainment and release of module temperature was related with material properties of PV module technologies. The amorphous module gave 5.7%, 2.7% and 15.0% more yearly average open-circuit voltage than polycrystalline, monocrystalline and thin film modules. Besides that, the thin film modules gave 6.5% and 1.7%, 9.3% and 4.0%, and 11.3% and 8.8% more yearly average normalized short-circuit current and power output than polycrystalline, monocrystalline and thin film modules respectively. It was shown that the maximum annual average open-circuit voltage was given by amorphous modules and maximum short-circuit current and power output by thin film modules during the study period.